Effects of Microencapsulated Probiotics on Performance, Organ Development, Diarrhoea Incidences, Blood Parameters, Intestinal Histomorphology and Microflora in Weaning Piglets - Nicoleta Aurelia Lefter; Mihaela Hăbeanu; Anca Gheorghe; Mihaela Dumitru; Claudiu Gal; Petru Alexandru Vlaicu (Agriculture, 2022)
The study aimed to assess the effects of the dietary supplementation of microencapsulated L. acidophilus and L. plantarum and their combination on the growth performance, organ development, diarrhoea incidences, blood profiles, intestinal histomorphology and microflora in weaned piglets. For that, 160 piglets with an average body weight (BW) of 8.52 ± 0.15 kg were divided into four groups (40 piglets/group) and allotted to one of the four dietary treatments as follows: a basal diet (C diet) or a basal diet containing 1 × 108 CFU/g of L. acidophilus (LA diet), or a diet containing 3 × 108 CFU/g of L. plantarum (LP diet) and a diet with the combination of both bacterial strains (LA + LP diet) for 21 days. On day 14, probiotics significantly increased ADFI, while FCR was higher in the LA and LP groups than the C and LA + LP groups. No effects (p > 0.05) on visceral organs weight, intestinal pH and biochemical parameters among treatments were noticed. Treatments significantly lowered diarrhoea incidence compared to control. Villus width was greater (p < 0.05) in all small intestinal segments in piglets fed probiotics. In the jejunum and ileum villus length, crypt length, and total villi length were higher (p < 0.05), particularly in the LA + LP group. The probiotics, particularly the LA + LP group, modulated the cecal, jejunum and ileum microbial community structure and increased (p < 0.05) the amount of Lactobacillus spp. while decreasing the populations of Escherichia coli and Staphylococcus. Our results indicated that dietary supplementation of microencapsulated probiotics, particularly the combination of L. plantarum and L acidophilus strains, maintained growth performance, lowered diarrhoea incidence and beneficially altered the intestinal architecture and microbial populations of weaned piglets.